The impact of p53 on DNA damage and metabolic activation of the environmental carcinogen benzo[a]pyrene: effects in Trp53(+/+), Trp53(+/-) and Trp53(-/-) mice - Krais, Annette M; Speksnijder, Ewoud N; Melis, Joost P M; Indra, Radek; Moserova, Michaela; Godschalk, Roger W; van Schooten, Frederik-J; Seidel, Albrecht; Kopka, Klaus; Schmeiser, Heinz H; Stiborova, Marie; Phillips, David H; et al. (Archives of toxicology, 2016)
The tumour suppressor p53 is one of the most important cancer genes. Previous findings have shown that p53 expression can influence DNA adduct formation of the environmental carcinogen benzo[a]pyrene (BaP) in human cells, indicating a role for p53 in the cytochrome P450 (CYP) 1A1-mediated biotransformation of BaP in vitro. We investigated the potential role of p53 in xenobiotic metabolism in vivo by treating Trp53(+/+), Trp53(+/-) and Trp53(-/-) mice with BaP. BaP-DNA adduct levels, as measured by (32)P-postlabelling analysis, were significantly higher in liver and kidney of Trp53(-/-) mice than of Trp53(+/+) mice. Complementarily, significantly higher amounts of BaP metabolites were also formed ex vivo in hepatic microsomes from BaP-pretreated Trp53(-/-) mice. Bypass of the need for metabolic activation by treating mice with BaP-7,8-dihydrodiol-9,10-epoxide resulted in similar adduct levels in liver and kidney in all mouse lines, confirming that the influence of p53 is on the biotransformation of the parent compound. Higher BaP-DNA adduct levels in the livers of Trp53(-/-) mice correlated with higher CYP1A protein levels and increased CYP1A enzyme activity in these animals. Our study demonstrates a role for p53 in the metabolism of BaP in vivo, confirming previous in vitro results on a novel role for p53 in CYP1A1-mediated BaP metabolism. However, our results also suggest that the mechanisms involved in the altered expression and activity of the CYP1A1 enzyme by p53 in vitro and in vivo are different.
Keywords: Microsomes, Liver; metabolická aktivace; mutantní kmeny myší; poškození DNA; Carcinogens, Environmental; adukty DNA; Male; DNA adducts; DNA Damage; Inactivation, Metabolic; Cytochrome P-450 CYP1A1; Benzo[a]pyrene; benzopyren; metabolická inaktivace; Kidney; cytochrom P-450 CYP1A1; mužské pohlaví; nádorový supresorový protein p53; karcinogeny životního prostředí; Benzo(a)pyrene; Cytochrome P450; NAD(P)H dehydrogenasa (chinon); Animals; ledviny; zvířata; DNA Adducts; Tumor Suppressor Protein p53; myši inbrední C57BL; Mice, Inbred C57BL; Activation, Metabolic; Tumour suppressor p53; Carcinogen metabolism; Mouse models; NAD(P)H Dehydrogenase (Quinone); jaterní mikrozomy; Mice, Mutant Strains